The Algorithm of Piousness: Emotional Engagement, Informal Islamic Religious Learning, and Pedagogical Patterns in YouTube Comments on Islamic Lecture Videos - Rika Azizah; Merri Sri Hartati; Lety Febriana (PT. Publikasiku Academic Solution, 2026)
YouTube has become a major platform for informal Islamic religious learning among Generation Z in Indonesia, yet the pedagogical dynamics within the comment sections of Islamic lecture videos remain underexplored. The 2017 Indonesia Demographic and Health Survey (IDHS) reported that 7.7% of adolescents had engaged in premarital sexual relations, highlighting the need to strengthen character-based Islamic education. This study analyzes 4,689 comments on three Islamic lecture themes aligned with the Grade X Senior High School Islamic Religious Education (PAI) curriculum: Guarding Social Relations, Guarding the Heart and Self-Dignity, and Avoiding Illicit Relationships. A computational-qualitative mixed-methods approach employed a ten-category Islamic Pedagogical Engagement (IPE) framework grounded in tarbiyah, ta'lim, ta'dib, and Krathwohl's affective taxonomy. Supplication for Self-Protection and Forgiveness was the dominant category (36.8%, n=1,727), followed by Repentance and Commitment to Avoiding Sin (22.2%, n=1,041) and Emotional Moving and Remorse (17.1%, n=803). Four Pedagogical Conversion Narrative (PCN) subtypes were identified, with highly appreciated comments describing digital lectures as divine guidance and expressing intentions to abandon dating relationships, although these self-reports require further verification. The findings demonstrate that YouTube comments function as an informal Islamic learning space where emotional engagement supports pedagogical depth. This relationship is conceptualized through the Digital Islamic Pedagogical Engagement (DIPE) model, offering implications for assessment and curriculum development in Grade X Islamic Creed and Character education.